2D Metal–Organic Frameworks Derived Nanocarbon Arrays for Substrate Enhancement in Flexible Supercapacitors. Issue 43 (27th October 2017) - Liu, Ximeng; Guan, Cao; Hu, Yating; Zhang, Lei; Elshahawy, Abdelnaby M.; Wang, John
Abstract: Direct assembling of active materials on carbon cloth (CC) is a promising way to achieve flexible electrodes for energy storage. However, the overall surface area and electrical conductivity of such electrodes are usually limited. Herein, 2D metal–organic framework derived nanocarbon nanowall (MOFC) arrays are successfully developed on carbon cloth by a facile solution + carbonization process. Upon growth of the MOFC arrays, the sites for growth of the active materials are greatly increased, and the equivalent series resistance is decreased, which contribute to the enhancement of the bare CC substrate. After decorating ultrathin flakes of MnO2 and Bi2 O3 on the flexible CC/MOFC substrate, the hierarchical electrode materials show an abrupt improvement of areal capacitances by around 50% and 100%, respectively, compared to those of the active materials on pristine carbon cloth. A flexible supercapacitor can be further assembled using two hierarchical electrodes, which demonstrates an energy density of 124.8 µWh cm −2 at the power density of 2.55 mW cm −2 . Abstract : A 2D nanowall array of metal–organic frameworks (MOF)‐derived nanocarbon is fabricated on a flexible substrate for improvement of energy storage properties. The surface area and electrical conductivity of MOF‐derived nanocarbon‐decorated substrate is increased, and hierarchical electrodes fabricated with active materials and MOF‐derived nanocarbon show great enhancement on areal capacitance.